Odpowiedź :
sin30stopni + 2 tg do kwadratu 60 stopni
____________________________________ =
(1 - sin 45 stopni) ( 1 + cos 45 stopni)
[½+2*(√3)²] / [ (1-√2/2)*(1+√2/2) ] = [½*6] / [1+√2/2-√2/2-2/4] = [3]/[1-2/4] = [3]/[2/4] = 3:½ = 3*2 = 6
____________________________________ =
(1 - sin 45 stopni) ( 1 + cos 45 stopni)
[½+2*(√3)²] / [ (1-√2/2)*(1+√2/2) ] = [½*6] / [1+√2/2-√2/2-2/4] = [3]/[1-2/4] = [3]/[2/4] = 3:½ = 3*2 = 6
jak to rozwiazac?
1.
sin30stopni + 2 tg do kwadratu 60 stopni
____________________________________________ =
(1 - sin 45 stopni) ( 1 + cos 45 stopni)
1/2+2*3
-------------------------=
(1-√2/2)(1+√2/2)
1/2+2*3
-------------------------=
1-2/4
1/2+2*3
-------------------------=
1/2
1+4*3=13
1.
sin30stopni + 2 tg do kwadratu 60 stopni
____________________________________________ =
(1 - sin 45 stopni) ( 1 + cos 45 stopni)
1/2+2*3
-------------------------=
(1-√2/2)(1+√2/2)
1/2+2*3
-------------------------=
1-2/4
1/2+2*3
-------------------------=
1/2
1+4*3=13